ÐšÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ðµ ÐºÐ»ÐµÑ‚ÐºÐ¸ Ñ…Ð¾Ñ€Ð¸Ð¾Ð½Ð° â€“ Ð¿ÐµÑ€ÑÐ¿ÐµÐºÑ‚Ð¸Ð²Ð½Ñ‹Ð¹ Ð¾Ð±ÑŠÐµÐºÑ‚ Ð´Ð»Ñ Ð±Ð¸Ð¾Ñ‚ÐµÑ…Ð½Ð¾Ð»Ð¾Ð³Ð¸Ð¸ - Goncharuk, E. I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
The possibility of cryopreserved chorion cell aplication for damaged cartilage restoration and burn therapy was demonstrated in experimental investigation.